Cues disseminated by professional associations across five professions and five nations: A lexical analysis of tweets (Preprint) - Sharon Williams (Journal of Medical Internet Research, 2023)
Background:Collaboration across healthcare professions is critical in efficiently and effectively managing complex and chronic health conditions. Yet interprofessional care does not happen automatically. Professional associations have a key role in setting a professions’ agenda, maintaining professional identity, and establishing priorities. Associations’ external communication is commonly undertaken through social media posts, such as Twitter. Despite the valuable insights potentially available into professional associations through such communication, to date, their messaging has not been examined.Objective:To identify the cues disseminated by professional associations that represent five healthcare professions, spanning five nations.Methods:Using a back-iterative application programming interface (API) methodology, tweets were sourced from professional associations that represent five healthcare professions that have key roles in community-based healthcare – namely, general practice, nursing, pharmacy, physiotherapy, and social work. Furthermore, the professional associations spanned Australia, Canada, New Zealand, the United Kingdom, and the United States of America. A lexical analysis was conducted of the tweets using Leximancer to clarify relationships within the discourse.Results:Following a lexical analysis of 50,638 tweets, seven key findings were identified. First, the discourse was largely devoid of references to interprofessional care. Second, there was no explicit discourse pertaining to physiotherapists. Third, although all the professions represented within this study support patients, discourse pertaining to general practitioners was most likely to be connected with that pertaining to ‘patients’. Fourth, tweets pertaining to pharmacists were most likely to be connected with tweets pertaining to ‘latest’ and ‘research’. Fifth, tweets about social workers were unlikely to be connected with discourse pertaining to, ‘health’ or ‘care’. Sixth, notwithstanding a few specific exceptions, the findings across the different nations were generally similar, suggesting their generality. Seventh, tweets pertaining to physiotherapists were most likely to refer to discourse pertaining to ‘profession’.Conclusions:The findings indicate that healthcare professional associations do not use social media to disseminate cues that reinforce the importance of interprofessional care. Instead, they largely use this platform to emphasize what they individually deem to be important and advance their respective profession’s interests. There is therefore considerable opportunity for professional associations to assert how the profession they represent complements other healthcare professionals, and how the professionals they represent can enact interprofessional care for the benefit of patients and carers.